Calculation of the Rate Constants of Vacuum Residue Hydrogenation Reactions in the Presence of a Chrysotile/NiTi Nanocatalyst - Nazerke Balpanova; Murzabek Baikenov; Assanali Ainabayev; Aikorkem Kyzkenova; Gulzhan Baikenova; Almas Tusipkhan (Fuels)
The paper presents the results of an investigation into the kinetics of catalytic hydrogenation of vacuum residue at temperatures of 380, 400 and 420 °C and different durations, ranging from 30 to 70 min, using a nanocatalyst containing the active metals nickel and titanium supported on chrysotile. It was found that the yield of oils from 30 to 50 wt.% and tars from 12 to 18 wt.% increased with increasing temperatures and reaction times. A slight increase in the proportion of solids in the range of 2.0 to 6.0 wt.% is explained by the activity of the nanocatalyst used. In the study of the kinetics of vacuum residue hydrogenation, using the nanocatalyst developed by the authors, we were able to achieve a low yield of solids with a short contact time as well as a high yield of low-molecular-weight compounds such as oils and tars. To determine the kinetic parameters (rate constants and activation energies), Simpson’s integral method and a random search engine optimization method were used. High values of rate constants are characteristic of reactions in the formation of oils k1, tars k2 and asphaltenes k3 in the temperature range of 380–420 °C. The high values of the rate constants k1, k2 and k3 in the catalytic hydrogenation of the vacuum residue indicate the high reaction rate and activity of the nanocatalyst used. With an increase in temperature from 380 to 420 °C, the rate constant of the formation of gas products from vacuum residue and the conversion of asphaltenes into oils significantly increase, which indicates the accumulation of low-molecular-weight compounds in oils. The activation energy for reactions leading to the formation of oils, tars, asphaltenes, gas and solid products was 75.7, 124.8, 40.7, 205.4 and 57.2 kJ/mol, respectively. These data indicate that the processes of vacuum residue hydrogenation with the formation of oils and asphaltenes require the lowest energy inputs. Reducing the process temperature to increase the selectivity of the vacuum residue hydrogenation process when using the prepared nanocatalyst is recommended. The formation of oils at the initial stage plays a key role in the technology of the heavy hydrocarbon feedstock (HHF) hydrogenation process. Perhaps the resulting oils can serve as an additional solvent for high-molecular-weight products such as asphaltenes, as evidenced by the low activation energy of the process.